Pengaruh Serum yang Disimpan Selama Lima Hari Suhu 2-8°C dengan Serum yang Diperiksa Langsung pada Pemeriksaan Kolesterol Total: The Effect of Serum Stored for Five Days Temperature of 2-8°C with Serum That is Checked Directly on Total Cholesterol Testing - Chalies Diah Pratiwi; Hariyanto Hariyanto; Andyanita Hanif Hermawati; Intan Niawati Fajrin (Borneo Journal of Medical Laboratory Technology, 2022)
Examination of blood cholesterol at this time became the trend of laboratory examination that much in demand by most people because of many diseases caused by hypercholesterolemia due to wrong diet or high cholesterol levels. Damaged equipment, reagent exhaustion, a large number of samples, laboratory distance with the sampling site too far, and power outages resulted in delayed laboratory examination that required sample storage. This study aimed to determine the effect of serum storage for five days with a serum examined directly to examine total cholesterol. The research design used was an experiment. The population in this research is all female students; Level 3 Study Program D3 Health Analyst STIKes Hutama Abdi Husada Tulungagung, using the Purposive sampling technique, counted 15 respondents. This research was conducted in May 2018. The data obtained were processed using SPSS 16 software and analyzed by Paired t-Test. This study showed the average value of total cholesterol levels in serum examined directly at 163 mg/dl while stored for five days temperature of 2-8 ° C at 158 mg/dl. After the paired test obtained value of P-value = 0.000, so P-value = 0.000 <α = 0.05, it can be concluded there is an influence between total cholesterol levels are checked directly and stored for five days temperature 2-8°C. Five days of serum storage affects the results of total cholesterol tests that lead to a decrease in total cholesterol, but the reduction is insignificant.